Strategic Flexibility: Navigator Industri dalam Mencapai Competitive Advantages - Herman, Robert Tang (Journal the Winners: Economics, Business, Management, and Information System Journal, 2008)
Article to describe how to develop a strategic flexibility as company responses and strategy in facing the government regulation of Standard Euro 2. Article also discussed the new product development concept based on market perspective. Research analysis was a descriptive statistic with a simple random sampling from a number of populations. The result describes that the government regulation of Standard Euro2 is supported and positively responses by industry and market. In spite of this, strategic flexibility is an approach to reach industry competitive advantage in term of product development strategy.